Penyelesaian Sengketa Konstruksi Pembangkit Listrik Tenaga Air melalui Dewan Sengketa Tetap: Studi Kasus PLTA Asahan 3 - Wisatrioda, Bayu; Sebastian, Reza Rafly; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
Electricity deficits in North Sumatra have hindered regional economic growth. The Asahan 3 HEPP, a national strategic project, was constructed to address this crisis. However, the Lot I Civil Works contract encountered complexities, resulting in 25 contractor claims within the first 20 months. This study analyzes the effectiveness of the SDB in resolving construction disputes at the Asahan 3 HEPP following a contract amendment. Employing a qualitative case study with a descriptive-analytical approach, the research examines the dynamics of dispute resolution before and after SDB activation. Primary data were gathered through interviews and observations, while secondary data were sourced from project documents and relevant legal literature. The findings indicate that the Engineer’s Determination proved ineffective, with only one claim resolved prior to the amendment. Contract Amendment No. 1 activated the SDB clause in accordance with the FIDIC Harmonised Edition 2010 General Conditions, replacing the previously implemented Ad-hoc mechanism. Post-amendment, the SDB, comprising independent experts, successfully issued five formal opinions, resolving all 25 contractor claims. This success was underpinned by the competence of the SDB members, their comprehensive understanding of the project, and the efficiency of the procedures. The study concludes that SDB activation was a strategic step that minimized conflict escalation. The SDB contributed significantly, effectively, and efficiently to the resolution of construction disputes at the Asahan 3 HEPP, aligning with Law Number 30 of 1999 and Law Number 2 of 2017.